Persepsi Dan Tingkat Partisipasi Masyarakat Terhadap Imunisasi Setelah Kejadian Vaksin Palsu Di Perumahan Taman Laguna Indah Kota Batam - Suci Fitriani Sammulia; Arie Vonie Kartika; Desy Maniarti Gusmali; Nurlia Oktaviyani (Lembaga Pengembangan Kinerja Dosen, 2022)
One type of effort to provide immunity to children is by inserting vaccines into the body to make anti-substances to prevent certain diseases. Vaccines are ingredients used to stimulate the formation of anti-substances, which are injected into the body by injection. In June 2016, it was revealed the case of making fake vaccines that were troubling the public. People's concern grew when they learned the fact that there had been a fake vaccine manufacturing for approximately 13 years. The existence of cases of fake vaccines that have been circulating, of course, will lead to different perceptions regarding the administration of vaccines to children. The purpose of this study is to find out how perceptions and levels of community participation in immunization after the case of a fake vaccine in Taman Laguna Indah Housing, Batam. This type of research is non experimental. This research method is descriptive method. The number of samples in this study were 50 respondents. The conclusion of the research conducted is the distribution of the level of knowledge, perceptions and participation of respondents, namely: respondents 'knowledge is categorized well with a percentage (80%), respondents' perceptions can be categorized quite well with a percentage (68%), and respondent participation can also be categorized quite well , it's just a lower percentagevalue(56%).